Technologies of the self in public health: insights from public deliberations on cognitive and behavioural enhancement. Issue 3 (27th May 2017) - Lehoux, P.; Williams-Jones, B.; Grimard, D.; Proulx, S.
Abstract: The aim of this paper is to examine how members of the public define the legitimacy of cognitive and behavioural enhancement. Our study involved a two-step multimedia-based deliberative intervention in which participants of different age groups pondered the desirability of a fictional enhancement technology: a sweater made of 'smart' textiles that provide 'bio-psycho-feedback' (PBF) to its user. A 3-min video clip presenting the fictional technology was used to stimulate deliberations in four face-to-face workshops ( n  = 38). A larger group of participants ( n  = 57) then discussed, in an online forum, two short stories illustrating dilemmas raised by the PBF sweater. Qualitative analysis of transcripts of the workshops and the forum identified patterns of moral argumentation in the reasoning processes by which participants challenge the PBF sweater's legitimacy: (1) when a shift in purpose occurs – from therapeutic to enhancement – and (2) when it engenders a shift in the user's sense of self – from an autonomous self to a socially coerced individual. These findings add nuance to current knowledge on public perceptions of cognitive and behavioural enhancement, providing insight into the ways that people conceive of the tension between autonomy and social coercion.